3
$\begingroup$

Let $f(x,y)$ be a function satisfying the condition $$ f(x,y) = f(2x + 2y, 2y - 2x) $$ with $x, y \in \mathbb{R}$. Now we define a function $g(x) := f(2^x, 0)$.

Decide if $g(x)$ is periodic or not. If it is, find its period.

Attempt: I didn't get the approach. I didn't understand the function. I found $g(x) = f(2^{x+1}, -2^{x+1})$. But got confused as to what to do next.

$\endgroup$
0
3
$\begingroup$

For all $a$, we have \begin{align*} f(a,0)&=f(2a,-2a)\\[4pt] &=f(0,-2^3a)\\[4pt] &=f(-2^4a,2^4a)\\[4pt] &=f(-2^6a,0)\\[4pt] &=f(b,0)\;\;\;\text{[letting $b=-2^6a$]}\\[4pt] &=f(-2^6b,0)\\[4pt] &=f(-2^6(-2^6a),0)\\[4pt] &=f(2^{12}a,0)\\[4pt] \end{align*} hence, letting $a=2^x$, we get $$g(x)=f(2^x,0)=f(a,0)=f(2^{12}a,0)=f(2^{12}2^x,0)=f(2^{x+12},0)=g(x+12)$$ so $g$ is periodic.

$\endgroup$
4
  • $\begingroup$ Why do I do that until I get $2^{12}$? How do I know where to stop? Do we apply it again and again until we get $2^x$ form? $\endgroup$
    – Iceberry
    Jun 17 '18 at 13:06
  • $\begingroup$ Some initial experimentation can hopefully reveal a pattern. The fact that powers of $2$ appear as coefficients lends support to the possibility that iteratively applying the specified rule to $g(x)$ will lead to an expression of the same form as the initial one. $\endgroup$
    – quasi
    Jun 17 '18 at 16:44
  • 1
    $\begingroup$ Also note: Iteration on $f(a,0)$ is less cumbersome than iteration on $f(2^x,0)$. $\endgroup$
    – quasi
    Jun 17 '18 at 16:47
  • 1
    $\begingroup$ In my latest edit, the fact that line $4$ yields $f(a,0)=f(-2^6a,0)$ suggests iterating that identity (since the zero part will stay fixed). $\endgroup$
    – quasi
    Jun 17 '18 at 17:16
2
$\begingroup$

Define $h\colon \Bbb C\to \Bbb R$ as $h(z)=f(\operatorname{Re}z,\operatorname{Im}z)$, i.e., $h(x+iy)=f(x,y)$. From $(2x+2y)+(2y-2x)i=2(x+iy)(1-i)$, we see that $h(z)=h(wz)$ with $w:=2(1-i)$. by induction, $h(z)=h(w^nz)$ for all $n\in\Bbb N$. Now from $(1-i)^2=-2i$, we see $\bigl(2(1-i)\bigr)^8=2^8\cdot (-2)^4i^4=2^{12}$. Hence $h(z)=h(2^{12}z)$, which translates to $f(x,y)=f(2^{12}x,2^{12}y)$ and $g(x)=g(x+12)$. Hence $12$ is a period of $g$.

Note that it is possible that $g$ also has smaller periods than $12$, for example, $f,h,g$ might be constant. In fact, the only functions with $h(z)=h(wz)$ for all $z$ that are continuous at $z=0$ are the constants. But if we do not require $f$ to be continuous, we can define $g$ arbitrarily (hence certainly without any smaller period) on, say, $[0,12[$, then obtain from that a partial definition of $h$ on $[1,2^{12}[$, can define $h$ arbitrarily in the remainder of the quadrangle with vertices $1,2^{12}, 2-2i, 2^{13}-2^{13}i$ (except that the values at the edges must match), can use $h(wz)=h(z)$ to extend $h$ to $\Bbb C\setminus\{0\}$, and define $ h(0)$ arbitrarily. This will give us an $f$ with $f(x,y)=f(2x+2y,2y-2x)$ such that the $g$ derived from it assumes the values on $[0,12[$ that we started with.

$\endgroup$
1
  • $\begingroup$ I didn't understand this back in last June. But, now I do and it is brilliant. Thank you. $\endgroup$
    – Iceberry
    Mar 29 '19 at 7:03
1
$\begingroup$

We have $$f(x,y)=f(2x+2y,2y-2x)=f(2(2x+2y+2y-2x),2(2y-2x-2y-2x))=f(8y,-8x)$$

Again applying it we get $$f(x,y)=f(8(-8x),-8(8y))=f(-2^6x,-2^6y)=f(-2^6(-2^6x),-2^6(-2^6y))=f(2^{12}x,2^{12}y)$$

Now we have $g(x)=f(2^x,0)=f(2^{12}2^x,0)=g(x+12)$. Thus $g$ is periodic. One possible period being $12$.

$\endgroup$
2
  • $\begingroup$ Do we apply it again to get $2^x$ form? $\endgroup$
    – Iceberry
    Jun 17 '18 at 13:07
  • $\begingroup$ yeah after deducing $f(x,y)=f(2^{12}x,2^{12}y)$ set $x=2^x$ and $y=0$ $\endgroup$
    – user428700
    Jun 18 '18 at 2:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.